Efficiency and Effectiveness of Islamic Microfinance toward Poverty Alleviation in Indonesia : Insights from Scholars and Experts - Arif Rahman, Hakim; Rossazana, Ab Rahim (Human Resource Management Academic Research Society (HRMARS), 2024)
This study examines the perspectives of experts and Muslim scholars on the efficiency and effectiveness of Islamic microfinance in alleviating poverty in Indonesia. Utilizing a qualitative approach, in-depth interviews were conducted with various scholars and experts in Indonesia. The data were analyzed using NVivo, a computer-assisted qualitative data analysis software. The research delves into the multifaceted nature of Islamic microfinance, which integrates profit-oriented goals with a fundamental social mission based on Islamic economic principles. It emphasizes prioritizing Islamic microfinance institutions' social mission and achieving financial sustainability. The study highlights the critical role of financial efficiency in maximizing profits and fostering innovation within Islamic microfinance. Moreover, it advocates redefining conventional efficiency metrics to align with Islamic economic principles. Additionally, the study discusses incorporating cash waqf instruments in fundraising to achieve financial and social efficiency, stressing the importance of professional management. Social efficiency is realized through profit-loss-sharing financing, while the effectiveness of poverty alleviation efforts relies on the competency and integrity of human resources within Islamic microfinance institutions. Ultimately, the study illuminates the complex interplay between financial sustainability and societal impact, underscoring the crucial role of institutional ownership in shaping priorities within Islamic microfinance.